2019
DOI: 10.7717/peerj.6788
|View full text |Cite
|
Sign up to set email alerts
|

Gastrocnemius fascicles are shorter and more pennate throughout the first month following acute Achilles tendon rupture

Abstract: The purpose of this study was to characterize the short-term effects of Achilles tendon ruptures on medial gastrocnemius. We hypothesized that the fascicles of the medial gastrocnemius muscle of the injured Achilles tendon would be shorter and more pennate immediately following the injury and would persist throughout 4 weeks post-injury. B-mode longitudinal ultrasound images of the medial gastrocnemius were acquired in 10 adults who suffered acute Achilles tendon ruptures and were treated non-operatively. Ultr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…This was accompanied by limited MTJ displacement throughout the same ROM ( Figure 3B). These results are comparable to previous short-term measurements that found consistently shorter fascicle lengths and lower muscle thickness up to 4 weeks post-ATR when held in plantarflexion (Hullfish et al, 2019). This appears to be consistent throughout the rehabilitation of gait, suggesting that current post-operative rehabilitative exercise do not appear to induce muscle adaptations on fascicle length in the affected MTU.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was accompanied by limited MTJ displacement throughout the same ROM ( Figure 3B). These results are comparable to previous short-term measurements that found consistently shorter fascicle lengths and lower muscle thickness up to 4 weeks post-ATR when held in plantarflexion (Hullfish et al, 2019). This appears to be consistent throughout the rehabilitation of gait, suggesting that current post-operative rehabilitative exercise do not appear to induce muscle adaptations on fascicle length in the affected MTU.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, muscle remodeling following ATR injury is rapid compared to the rate of tendon healing, which can last as long as 1 year (Sharma and Maffulli, 2005). Sideto-side differences in muscle morphology are apparent soon after ATR, as Hullfish and colleagues have recently reported that medial gastrocnemius fascicles on the ATR-injured side remain both shorter and more pennate within 1 month postinjury (Hullfish et al, 2019). Recent findings suggest that further muscle remodeling occurs after this time, with increases in medial gastrocnemius volume found between 6 and 26 weeks after ATR (Eliasson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Acute Achilles tendon ruptures have been shown to elicit shorter and more pennate gastrocnemius muscle fascicles at rest (13). This muscle reconfiguration persists through at least 4 wk when the Achilles tendon rupture is treated nonsurgically (13). Additionally, we reported that long-term functional deficits were explained by permanent reductions in fascicle length and increases in pennation angle in a case study (2).…”
Section: Introductionmentioning
confidence: 83%
“…Gastrocnemius muscle remodeling occurs following Achilles tendon ruptures (13,21), which appears to be in response to a sudden loss of muscle-tendon tension. Acute Achilles tendon ruptures have been shown to elicit shorter and more pennate gastrocnemius muscle fascicles at rest (13). This muscle reconfiguration persists through at least 4 wk when the Achilles tendon rupture is treated nonsurgically (13).…”
Section: Introductionmentioning
confidence: 99%
“…Force-length characteristics have been demonstrated in humans in vivo (Maganaris, 2001), however, these results were only reported in isometric contractions. Despite evidence of variations in muscle structure between different populations of human subjects (Abe et al, 2000; Hullfish et al, 2019a; Kearns et al, 2000; Kubo et al, 2003; Lee and Piazza, 2009), there are few studies reporting the relationship between variations in resting fascicle length or pennation angle and dynamic muscle function in humans (Ema et al, 2016). Outside of the plantar flexors, one study found that elbow extensor velocity under no load was positively correlated with muscle volume and pennation angle but not muscle length (Wakahara et al, 2013).…”
Section: Discussionmentioning
confidence: 99%